Double-stranded RNA and Toll-like receptor activation: a novel mechanism for blood pressure regulation. (30th January 2020) - Dela Justina, Vanessa; Giachini, Fernanda R.; Priviero, Fernanda; Webb, R. Clinton
Abstract: Toll-like receptors (TLRs), such as TLR4 and 9, recognize pathogen-associated molecular pattern (PAMPs) and danger-associated molecular patterns (DAMPs) and are associated with increased blood pressure (BP). TLR3, residing in the endosomal compartment, is activated by viral double-stranded RNA (dsRNA) leading to activation of TIR receptor domain-containing adaptor inducing IFN-β (TRIF) dependent pathway. Besides foreign pathogens, the immune system responds to endogenous markers of cellular damage such as mitochondrial dsRNA (mtdsRNA). New evidence has shown a link between dsRNA and increased BP. Moreover, TLR3 activation during pregnancy was demonstrated to develop preeclampsia-like symptoms in both rats and mice. Hence, we hypothesize that the dsRNA derived from viral nucleic acids or cellular damage (mtdsRNA) will increase the inflammatory state through activation of TLR3, contributing to vascular dysfunction and increased BP. Therefore, inhibition of TLR3 could be a therapeutic target for the treatment of hypertension with potential improvement in vascular reactivity and consequently, a decrease in BP.